Sistem Informasi Pengelolaan Update RME RSUP Dr. Kariadi Berbasis Web - Hadinata, Nova Oktaviani; Jananto, Arief (Jurnal Teknik Informatika UNIKA Santo Thomas, 2024)
Electronic Medical Records (RME) at Dr. Kariadi Central Hospital have been used since 2019. As technology develops and the use of RME applications increases, it has resulted in complaints and suggestions from users, to update the RME application to make it better in the future. But currently there is no information system to accommodate these problems. From these problems, a study was conducted to create an information system with the aim that users can document and manage the RME update process through the information system provided. This research uses the waterfall system development method, with the analysis system in the form of interviews and literature studies. As for the system design or modeling language using UML, and the programming language using PHP and MySql as storage / database. From the research conducted, an information system was produced that can document any complaints or suggestions from users, as well as monitoring for any related follow-up related to the RME application update.